2012
DOI: 10.1111/j.1571-9979.2012.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Mediation Research: A Current Review

Abstract: In this article, we review the mediation literature from the past decade, utilizing a cybernetic mediation paradigm to organize the material. In this paradigm, we note that the type of conflict, country, culture, and mediation institutions affect the mediation process. Within this process, the mediator and disputants interact with each other, attempting to reach their own goals. This interaction produces outcomes for the disputants, the mediators, and other parties. The literature -organized using this paradig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
156
0
21

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 175 publications
(184 citation statements)
references
References 71 publications
(66 reference statements)
7
156
0
21
Order By: Relevance
“…EU officials also possess considerable content expertise (Wall and Lynn 1993, Beach 2005, Tallberg 2006, Biermann and Siebenhüner 2009. Various CSDP services have already been mentioned.…”
Section: Bureaucratic Resourcesmentioning
confidence: 99%
“…EU officials also possess considerable content expertise (Wall and Lynn 1993, Beach 2005, Tallberg 2006, Biermann and Siebenhüner 2009. Various CSDP services have already been mentioned.…”
Section: Bureaucratic Resourcesmentioning
confidence: 99%
“…Furthermore to advance the efficacy of the field, it is crucial for mediators to have access to evidence-based information and evaluations about which mediation strategies work best in different situations. In sum, the field is lacking an integrative model, which would best enable empirical research to advance mediators' understanding of how to approach distinct types of mediation situations (Wall and Dunne, 2012).The current paper contributes to an ongoing program of research (Coleman et al, 2010(Coleman et al, , 2013(Coleman et al, , 2015(Coleman et al, , 2016 aimed at developing a new contingency model of adaptive mediation. It presents findings from two studies that further develop and support the utility of an adaptive or situationally contingent approach to mediation, where mediators learn to use alternative or enhanced strategies in response to fundamentally different challenges they face in mediations.…”
mentioning
confidence: 99%
“…This review revealed studies on various components of mediation, including aspects of the disputants (disputant power, power asymmetry, gender, motivation and commitment to mediation, hostility, conflict management style), the conflict (type of issues, intensity, resolution status, common ground and possibilities for mutually acceptable solutions), the mediation context (culture, environmental factors, public or private nature of the mediation, time pressure, rules and standards, past outcomes and number of parties), and -in particular -on aspects of the mediators themselves (mediator style, training, ideology, skill-base, expertise, experience and rank, mediator ties, the value the mediator places on the parties' attainment of their goals, knowledge and bias toward the parties and the clarity with which the mediator understands the mediator's role). Thus, the survey of mediation research revealed a broad array of factors affecting mediator behaviors and outcomes, but, as suggested by Wall and Dunne (2012), its disparate and piecemeal nature makes it difficult to deduce the major antecedents of differences in mediators' strategies beyond their personal preferences.Therefore, the next goal of Coleman et al (2015) was to attempt to reduce the multitude of antecedent factors from their review of the literature and empirically identify the most fundamental dimensions underlying the many factors. Accordingly, they conducted a survey study of 149 experienced mediators from various mediation domains (international, community, business, family, etc.)…”
mentioning
confidence: 99%
See 2 more Smart Citations